The Chinese are Here: Firm Level Analysis of Import Competition and Performance in Sub-Saharan Africa - Christian K. Darko; Giovanni Occhiali; Enrico Vanino (Fondazione Eni Enrico Mattei (FEEM), 2018)
This study uses firm level data on 19 Sub-Saharan Africa countries between 2004 and 2016 to provide a rigorous analysis on the impact of Chinese import competition on productivity, skills, and performance of firms., We measure import competition and ports accessibility at the city-industry level to identify the relevance of firms' location in determining the impact of Chinese imports competition. To address endogeneity concerns, a time-varying instrument for Chinese imports based on the interaction between an exogenous geographic characteristic and a shock in transportation technology is developed. The results show that imports competition has a positive impact on firm performance, mainly in terms of productivity catch-up and skills upgrading. Of particular interest is the finding that the effects of import competition from China are stronger for more remote firms that have lower port accessibility, an indication that Chinese imports in remote areas improves productivity of laggard firms, employment, and intensity of skilled workers. Our findings indicate that African firms are improving their performance as a consequence of the higher Chinese import intensity, mainly through direct competition and the use of higher quality inputs of production sourced from China.
Keywords: F16; F61; F63; R11; J21; J24; 330; Import Competition; Productivity Catch-up; Trade Infrastructure; Skills; Employment; Sub-Saharan Africa; China